Influence of chicory feeding on performance and gut development in broilers - Liu, Haoyu (2008)
Chicory is a fibre-rich plant with potential prebiotic capacity. In the present investigation, day-old broilers were fed in 27 days with eight different experimental diets. Different harvests time and levels of chicory and inclusion of inulin were tested of their influence on broiler performance. The histological approach was used to assess the gut development by measuring villus height and crypt depth.